Voices Unveiled: Navigating Intersectionality in the Political Landscape of Chinese Women in Peninsular Malaysia - Ramli, Nurul Asmaa binti; Kamalbatcha, Zainebbeevi binti; Saidon, Nor Rafidah binti; Hairi , Nur Atika Binti; Martin, Farahrina Francis (Journal of Ecohumanism, 2024)
This study explores the factors influencing Chinese women’s involvement in politics in Peninsular Malaysia, using qualitative interviews with ten participants selected via purposive sampling. Key informants include female political representatives, male politicians, academics and Non-Governmental Organization (NGO) activists. The research applies intersectionality theory to analyze how internal and external agents of political socialization and various challenges shape women’s political engagement and culture. Internal socialization agents encompass education, economic status, family background, religion, ethnicity, and gender. External agents include Non-Governmental Organizations (NGOs), political parties, and community networks. The study identifies multiple challenges that Chinese women face, such as gender competition, cronyism, low political interest, time management conflicts, racial sentiments, sexist remarks, male dominance, competition from political opponents, and ideological barriers. These agents and challenges are intertwined and impact Chinese women’s political culture, which, in turn, influences their empowerment in political, economic, and social spheres. The intersectionality framework reveals how overlapping social identities and systemic barriers shape their political experiences and efforts towards empowerment. This study provides insights into the complex dynamics affecting Chinese women’s political participation and highlights the need for comprehensive strategies to enhance their roles in politics and broader societal contexts.